KAJIAN YURIDIS PENJATUHAN PIDANA MINIMUM KHUSUS PADA TINDAK PIDANA CUKAI ROKOK MENURUT UNDANG-UNDANG CUKAI - Reviansyah Erlianto (YUSTISI, 2025)
The cigarette industry is one of the agroindustrial sectors which has quite a massive role in the Indonesian economy. But the problem is, the many violations against the implementation of excise revenue prove the need for improvements to the excise administration system and increase law enforcement efforts against excise violations. In addition, there are special minimum criminal provisions in the excise law indicating that certain considerations are needed by judges in deciding cases, this is certainly contrary to the principle of independence and the freedom of judges in making decisions. The normative juridical research method uses descriptive analytical methods in the form of elaborating some of the data collected through data collection in the form of library research and interview methods. The conclusion obtained is that the crime of excise duty violation is regulated in Article 50 to Article 62 of Law 39/2007. As well as the imposition of a special minimum sentence by law is the implementation of the principle of legality, even so the panel of judges must also consider juridical, sociological and philosophical aspects which aim to provide a sense of justice, benefit and legal certainty.